Modelling an orientation system based on speculative computation - Ramos, João Ricardo Martins (2014)
Progress is inherent to a living society, which may occur in several different areas (e.g. computation, healthcare) and manners. The present (or now) is the time that is associated with the events perceived directly and in the first time, making, for example, the society to be very inquisitive on assistive technologies and how they may improve the human beings quality of living. This application of scientific knowledge for practical purposes may help the user in his/her diminished capabilities, and, usually, implies a small adaptation on the part of the individual in the use of devices; indeed one of the die down potentials of people with cognitive disabilities is the one of spatial orientation. On the other hand several were the authors that have developed systems to help an human being to travel between two locations. However, once the system is set up the change in the configurations have to be done manually in order to better adjust the system to the user. In order to go round this drawback, in this work it is presented a framework of speculative computation to set up the computation of the next user step using default values. When the information is obtained the computation is revised. Thus, the system may have a faster reaction to the user stimulus or it may start warning the user before he/she takes the wrong direction.